2008
DOI: 10.1590/s1020-49892008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos dietéticos das refeições oferecidas por empresas participantes do Programa de Alimentação do Trabalhador na Cidade de São Paulo, Brasil

Abstract: More specific action is required targeting company officers and managers in charge of food and nutrition services, especially in companies without dietitian supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
0
9
0
22
Order By: Relevance
“…The greater amount of calories from oils and fats in workplace cafeteria meals is corroborated by a study that assessed the menu of companies in São Paulo and found the total fat content to be excessive 33 . However, the present study did not assess fat quality, and all study restaurants used vegetable oils for cooking.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The greater amount of calories from oils and fats in workplace cafeteria meals is corroborated by a study that assessed the menu of companies in São Paulo and found the total fat content to be excessive 33 . However, the present study did not assess fat quality, and all study restaurants used vegetable oils for cooking.…”
Section: Discussionmentioning
confidence: 85%
“…Soda and sweets are the first and third most consumed food items away from home in Brazil 20 , and companies in São Paulo frequently offer too much free sugar 33 .…”
Section: Discussionmentioning
confidence: 99%
“…9,14,16 In Brazil, these meals are generally planned out based on specifi c governmental programs and should, therefore, follow specifi c nutritional recommendations and even serve as tools for promoting health eating. In a study in the city of São Paulo, Southeastern Brazil, lunch was the meal most frequently eaten outside of the home.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao perfil antropométrico, as pesquisas indicam um quadro de excesso de peso entre os usuários do Programa (Geraldo, Bandoni, Jaime, 2008;Veloso, Santana, Oliveira, 2007;Sávio et al, 2005;Veloso, Santana, 2001;Burlandy, Anjos, 2001); já em relação aos cardápios ofertados, indicam sua inadequação (Geraldo, Bandoni, Jaime, 2008;Sávio et al, 2005;Moura, 1986).…”
Section: O Programa De Alimentação Do Trabalhador (Pat)unclassified